Arkæologiske undersøgelser i fire arabiske stater - Glob, P.V. (Kuml, 1959)
Archeological Investigations in Four Arab States. The Danish archeological investigations in the countries along the shores of the Arabian Gulf were continued in the spring of 1959, with excavations in the Principalities of Kuwait, Bahrain, Qatar and Abu Dhabi, and with reconnaissance extended to the western coast of the Oman peninsula and to the oases around Buraimi. 27 archeologists and assistants, and several hundred local labourers, took part in these investigations, with the author as Director and Geoffrey Bibby as Deputy Director. The main party left Denmark 13th January, and work commenced in Bahrain and Qatar 16th January, in Kuwait 20th January, and in Abu Dhabi 20th February. The season concluded at all sites about 1st April. In Bahrain previous years’ excavations at Bahrain’s prehistoric capital at Qala’at al-Bahrain were continued; Hans Berg and Karen Frifelt excavated further rooms in the large building 1), including one with remains of a ’throne’ (Fig 1), while at the city wall 2) Egon Hansen discovered a workshop for the stamp-seals characteristic of the Dilmun-culture of the Second and Third Millennia BC 3), so that they can now with certainty be regarded as characteristic types of the new culture group which ran the trade between the Sumerians in Mesopotamia and the Indus civilisation. In the temples at Barbar, Hellmuth Andersen and Peder Mortensen completed their investigations of the central core of the earliest stage 4), and on the western side uncovered new large constructional features. Here the uncovering of the western ramp 5) led to an important new discowery, at it was shown to lead down to a ’well-temple’, in the centre of which stood a stone vessel with three holes in the sides just above the bottom, to allow the subsoil-water to run out of it (Fig. 2). This ramp had been in use during both the first and second stages of the temple, and had thus not formed an entrance to the temple as was at first thought. This also gives a better explanation of the large stone blocks which lie in two rows on either side of the ramp, and in which we may assume that wooden figures of gods stood 6). In addition, Harald Andersen, Mogens Ørsnes and Knud Riisgård investigated four Iron-Age burial mounds south of the Budaiya road, discovering stone cists 7) containing, among other objects, pottery and glass. Frode Visti was in charge of the camp and of conservation. In Qatar the excavation was continued of a large town area at Murwab on the west side of the peninsula dating to the middle of the First Millennium BC, by Eigil Knuth and Knud Dalgaard-Knudsen, while Viggo Nielsen excavated several of the burial mounds at Umm alMa 8), and in addition carried out excavations on the Stone-Age settlement of Mesolithic date at Al-Wusail 9), characterized by a tanged blade-arrowhead of which about fifty, in addition to numerous fragments, were found. West of Al-Wakrah a new field of rock-carvings was investigated by P. V. Glob. The carvings consisted mainly of cup-marks arranged in patterns similar to those earlier found south of Al-Furaihah 10), though several new subjects were noted. This season the investigations in Qatar were extented to cover ethnographical studies by Klaus Ferdinand among the Na’im and Murra tribes (Fig. 3), while at the same time Mrs. Jette Bang took a documentary film in colour. On the island of Failaka in Kuwait excavation continued at the "tell" of Sa’ad on the southwest point of the island11 ), Dr. Aage Roussell, Dr. Åke Fredsjo, Oscar Marseen, Erik Spjæt Christensen and Jørn Glob taking part in the work. Here a series of dwelling-rooms was uncovered, and in them ridged pottery and 35 stamp-seals of steatite and blanks for seals show that the settlement belongs to the Dilmun culture and that this type of seal was also manufactured here. In the "tell" of Sa’aid nearby Erling Albrectsen, Georg Kunwald, Gunnar Lange-Kornbak and Arne Thorsteinsson dug in the remains of the Greek occupation 14). The large site here has proved to be an acropolis surrounded by ramparts and a deep moat, and containing a temple of which only a small portion has as yet been excavated (Fig. 4). Our investigations here were also assisted by Imran Abdo, of the Kuwait Museum. In Abu Dhabi, a burial tumulus and a contemporary settlement were investigated by Harald Andersen, Mogens Ørsnes and Knud Risgård on the island of Umm an-Nar, while the same team, together with Bibby and Glob, carried out a reconnaissance of’ the area around Buraimi, where a group of about 200 stone burial cairns was discovered at Nudud al-Jahal. The majority of these cairns were about two metres high and about 12 metres in diameter (Fig. 5). The reconnaissance was continued by Bibby and Glob from Buraimi northward through the western part of the Oman peninsula as far as Ras al-Khaimah. In the course of the journey flintsites and tells were located and mapped. As in previous years the investigations on Bahrain were made possible by a large grant from the Carlsberg Foundation in Copenhagen, while contributions were also received from the Government of Bahrain and the oil company BAPCO. For help and hospitality there we thank the Ruler of Bahrain, His Highness Sheikh Sulman bin Hamad Al-Khalifah, and His Excellency Sheikh Isa bin Sulman Al-Khalifah, the Secretary to the Government, Mr. G. W. R. Smith, and the Vice President of BAPCO, Mr. M. H. Lipp. The investigations on Failaka were financed by the Government of Kuwait, for which we thank the Ruler, His Highness Sheikh Abdullah AlSalim Al-Sabah, and the Minister of Education, His Excellency Sheikh Abdullah Al-Jabir Al-Sabah. In carrying out the work we were greatly assisted by the Director of Education, Mr. Abdulaziz Hussein, and the Deputy Director, Mr. Darwish Miqdadi. The work in Qatar was made possible by grants from local sources, and for them we are deeply grateful to the Ruler, His Highness Sheikh Ali bin Abdullah Al-Thani, and to the General Manager of the oil company QPC, Mr. P. R. A.Ensor, while much welcome assistance was rendered to us by the Adviser to the Government, Mr. G. M. Hancock, and by Sheikh Jasem bin Mohammed bin Jasem Al-Thani. In Abu Dhabi our work was followed with great interest by the Ruler, His Highness Sheikh Shakbut bin Sultan bin Zaid, and by His Excellency Sheikh Zaid bin Sultan bin Zaid, while we received invaluable assistance from the oil company ADMA, and from its representative in Abu Dhabi, Mr. I. Cuthbert. A colour film for BAPCO of the work of the expedition was taken this year by Mr. J. Underwood, while our work was introduced to a wider circle through Ib Rene of the Danish State Radio, Svend Aage Lorentz and Henning Bendtsen of Danish Television, and by Adam Wiehe, journalist, and Karl Bovin, artist, who was sent out by the Art Society of the Carlsberg Breweries. As in earlier years the Danish archeologists have, throughout the large area which our researches have gradually come to cover, everywhere been met with cordial hospitality and a ready willingness to assist from friends both old and new among the residents in these many lands. Their help has been of inestimable value to the progress and success of the expedition. P. V. Glob